Engineered silver nanoparticles are sensed at the plasma membrane and dramatically modify the physiology of Arabidopsis thaliana plants. (21st January 2016) - Sosan, Arifa; Svistunenko, Dimitri; Straltsova, Darya; Tsiurkina, Katsiaryna; Smolich, Igor; Lawson, Tracy; Subramaniam, Sunitha; Golovko, Vladimir; Anderson, David; Sokolik, Anatoliy; Colbeck, Ian; Demidchik, Vadim
Summary: Silver nanoparticles (Ag NPs) are the world's most important nanomaterial and nanotoxicant. The aim of this study was to determine the early stages of interactions between Ag NPs and plant cells, and to investigate their physiological roles. We have shown that the addition of Ag NPs to cultivation medium, at levels above 300 mg L −1, inhibited Arabidopsis thaliana root elongation and leaf expansion. This also resulted in decreased photosynthetic efficiency and the extreme accumulation of Ag in tissues. Acute application of Ag NPs induced a transient elevation of [Ca 2+ ]cyt and the accumulation of reactive oxygen species (ROS; partially generated by NADPH oxidase). Whole‐cell patch‐clamp measurements on root cell protoplasts demonstrated that Ag NPs slightly inhibited plasma membrane K + efflux and Ca 2+ influx currents, or caused membrane breakdown; however, in excised outside‐out patches, Ag NPs activated Gd 3+ ‐sensitive Ca 2+ influx channels with unitary conductance of approximately 56 pS. Bulk particles did not modify the plasma membrane currents. Tests with electron paramagnetic resonance spectroscopy showed that Ag NPs were not able to catalyse hydroxyl radical generation, but that they directly oxidized the major plant antioxidant, l ‐ascorbic acid. Overall, the data presented shed light on mechanisms of the impact of nanosilver on plant cells, and show that these include the induction of classical stress signalling reactions (mediated by [Ca 2+ ]cyt and ROS) and a specific effect on the plasma membrane conductance and the reduced ascorbate. Significance Statement: Silver nanoparticles are known antimicrobial and antifungal agents, and also affect diverse physiological functions in animal cells, but their intracellular effects on plant cells is largely unexplored. Here we show that silver nanoparticles induce stress signalling mediated by Ca2+ and reactive oxygen species, affect plasma membrane conductance and oxidise ascorbic acid.